Phytoremediation case study, Manhattan KS - Stiffarm, Ashley Marie (Kansas State University, 2015)
Contaminated water poses a major environmental and human health problem, which may be resolved by using the emerging phytoremediation technology. This plant-based cost-effective approach to remediation takes advantage of the ability of plants to concentrate elements and compounds from the environment, to absorb and transpire large amounts of water, and to metabolize various molecules in their tissues. The city of Manhattan’s Biosolids Farm located near Manhattan, Kansas is using the emerging technology of phytoremediation. The Biosolids Farm remediation began in the mid 1990’s; with a large planting of alfalfa with the goal of absorbing excess nitrates from soil and ground water. In 2004, hundreds of trees were planted, to serve as a protective buffer between the biosolids disposal area and the Kansas River. In 2006, a trench study was installed to improve tree establishment on a sandy outwash area close to the Kansas River using Siberian elm seedlings and rooted cottonwood cuttings from Nebraska and true cottonwood seedlings from Missouri. Treatments included trenching, dairy cattle composted manure, and tree shelters. This planting was done to serve as a vegetative barrier and to aid in reducing nitrate movement into the Kansas River. There were interaction between the tree sources and the trenching, compost and shelter treatments. The treatments showed significant interactions with tree sources with the addition of compost and shelters with a p value of 0.0438, and trenching and compost p-value 0.0021. Tree survival was significantly improved with the use of tree shelters.
Keywords: Biosolids; Populus spp; Trees; Nitrates; Trenching; Horticulture (0471)